A STUDY ON BENEFITS, CHALLENGES AND FACTORS OBSTRUCTING THE GROWTH OF E- COMMERCE IN BUSINESS WORLD - Bhaskar, Priyanka; Choudhary, Savita (The journal of contemporary issues in business and government, 2022)
In an expanding economy, information technology has played a critical role in the future expansion of trade sectors and business practices. The increased usage of smart mobile services and the internet as a new distribution channel for corporate transactions and international trading necessitates a greater focus on ecommerce security to reduce fraudulent activity. The advent of information and communication technology has resulted in numerous alterations in many aspects of a person's everyday life. E-commerce provides several advantages that increase consumer satisfaction by providing convenience in any location and allowing the firm to obtain a competitive edge over its competitors. This study foresees the conceptual framework of e-commerce, tools used in e-commerce platforms along its importance. In last part of the paper discussion done on the factors obstructing the growth of e-commerce which are considered potential difficulties in a developing economy. In conclusion, we found that there should be adequate market research and analysis for e-commerce. E-commerce does not go beyond the basic principles of good business planning and supply and need. E-commerce allows you to connect to the outside world.